Pigmented Hypertrichosis with Insulin-Dependent Diabetes Mellitus Syndrome: A Case Series - Jacobs, An; Cifelli, Paramita; Delbeck, Daniel; Elbarbary, Nancy; Gevers, Evelien; Sumnik, Zdenek; Amaratunga, Shenali Anne; Pundziute Lyckå, Auste; Casteels, Kristina; SWEET and DPV study group (Hormone research in paediatrics, 2025)
INTRODUCTION: Pigmented hypertrichosis with insulin-dependent diabetes mellitus (PHID) syndrome is a rare disease, and part of the cluster histiocytosis-lymphadenopathy plus syndrome (H syndrome), which is associated with mutations in the SLC29A3 gene. Patients with PHID show clinical features of H syndrome but also have insulin-dependent diabetes mellitus. The PHID has previously been described as predominantly in absence of pancreatic autoantibodies. Case Series Presentation: Through an open call in two international diabetes registers, clinical and genetic characteristics of 7 PHID patients in 6 treatment centres were collected after informed consent. All of them had consanguinity in their families, and their origins were located in North-African and Middle Eastern regions. Four out of 7 patients had at least one positive pancreatic autoantibody. DISCUSSION AND CONCLUSION: Our case series reveals that PHID exhibits a wide range of clinical symptoms and signs. When consanguinity is present in a patient with newly diagnosed diabetes, and/or if other atypical symptoms such as dysmorphic features, skin lesions, haematological abnormalities, and developmental delay are present, threshold for genetic analysis should be low. Moreover, the presence of autoantibodies should not withhold genetic testing as our case series contradicts the previous observation of predominant autoantibody absence in PHID.
Keywords: Hypertrichosis; předškolní dítě; Mutation; H syndrome; Child; Autoantibodies; hypertrichóza; Humans; lidé; mladiství; Diabetes; PHID syndrome; autoprotilátky; Female; Male; Nucleoside Transport Proteins; mutace; mužské pohlaví; Consanguinity; ženské pohlaví; Child, Preschool; Diabetes Mellitus, Type 1; proteiny přenášející nukleosidy; dítě; diabetes mellitus 1. typu; SLC29A3; pokrevní příbuzenství; Adolescent